Pendelegasian Kewenangan Penuntutan berdasarkan Pasal 18 Ayat 1 Undang - Undang Kejaksaan Dihubungkan dengan Pendelegasian Kewenangan Undang - Undang Nomor 30 Tahun 2014 tentang Administrasi Pemerintahan - Addrey Ben Vitahula Sihaloho; Abellio Jhose Sitompul (Deposisi: Jurnal Publikasi Ilmu Hukum, 2026)
This study aims to analyze the mechanism of delegation of prosecutorial authority within Indonesia’s criminal justice system and to examine its conformity with the principles of delegation of authority in administrative law. The Prosecution Service, as an institution adhering to the single prosecution system, plays a central role in law enforcement, with the Attorney General holding the highest prosecutorial authority. In practice, such authority is delegated to Public Prosecutors as part of efforts to enhance the effectiveness of law enforcement, while remaining grounded in the principle of legality and national law enforcement policies. This research employs a normative juridical method by combining a statutory and conceptual approaches, through the analysis of the Criminal Procedure Code, the Law on the Prosecution Service, and the Law on Government Administration. The findings confirm that the delegation of prosecutorial authority is normatively consistent with the principles of delegation, particularly in relation to the transfer of responsibility and accountability to the recipient of authority. However, in its implementation, challenges remain, particularly the disharmony of authority among law enforcement institutions such as the Corruption Eradication Commission and military courts, which may undermine the single prosecution system.